Encyclopaedia of physical education and sports Vol.9 The world of Baseball - Mudgal, Rahul (Ed); Kaushik, Vijaya (ed); Kaushik, Vijaya (Ed.) (New Delhi Sarup Book Publishers, 2012)
Baseball : The rememberence of things past